Forms of Care: Chimamanda Ngozi Adichie’s Americanah (2014), Agency, and Decolonial Feminism - McCann, Fiona (Études littéraires africaines, 2021)
This article explores feminist politics in Chimimanda Ngozi Adichie’s Americanah and the ways in which it interlinks with forms of care. I tease out the author’s engagement with intersectional feminism as well as her blind spots. I situate Adiche’s work within the context of postcolonial, popular and decolonial feminism, unpacking the significance of hair and the more general question of agency. I then move to show that the poetics of care developed in the novel ultimately falls short of embracing a decolonial feminist stance due to the relative invisibility of the neo-colonial structures at work in contemporary Nigeria.